Physician remuneration schemes, psychiatric hospitalizations and follow-up care: Evidence from blended fee-for-service and capitation models. (January 2021) - Vu, Thyna; Anderson, Kelly K.; Devlin, Rose Anne; Somé, Nibene H.; Sarma, Sisira
Abstract: Psychiatric hospitalizations could be reduced if mental illnesses were detected and treated earlier in the primary care setting, leading to the World Health Organization recommendation that mental health services be integrated into primary care. The mental health services provided in primary care settings may vary based on how physicians are incentivized. Little is known about the link between physician remuneration and psychiatric hospitalizations. We contribute to this literature by studying the relationship between physician remuneration and psychiatric hospitalizations in Canada's most populous province, Ontario. Specifically, we study family physicians (FPs) who switched from blended fee-for-service (FFS) to blended capitation remuneration model, relative to those who remained in the blended FFS model, on psychiatric hospitalizations. Outcomes included psychiatric hospitalizations by enrolled patients and the proportion of hospitalized patients who had a follow-up visit with the FP within 14 days of discharge. We used longitudinal health administrative data from a cohort of practicing physicians from 2006 through 2016. Because physicians practicing in these two models are likely to be different, we employed inverse probability weighting based on estimated propensity scores to ensure that switchers and non-switchers were comparable at the baseline. Using inverse probability weighted fixed-effects regressions controlling for relevant confounders, we found that switching from blended FFS to blended capitation was associated with a 6.2% decrease in the number of psychiatric hospitalizations and a 4.7% decrease in the number of patients with a psychiatric hospitalization. No significant effect of remuneration on follow-up visits within 14 days of discharge was observed. Our results suggest that the blended capitation model is associated with fewer psychiatric hospitalizations relative to blended FFS. Highlights: Blended capitation reduces psychiatric hospitalizations relative to blended FFS. Blended capitation reduces number of patients with a psychiatric hospitalization. Aftercare incentive claimed is similar across blended FFS and capitation models. Remuneration has no effect on follow-up within 14 days of a psychiatric discharge.